Factors Influencing Exclusive Breastfeeding in Developing Countries: A Review - Arfianti, Mariza; Retni, Retni (Penerbit Goodwood, 2023)
Purpose: The local government in many developing nations has struggled to encourage mothers to breastfeed their infants exclusively for up to 6 months. The goal of this review was to outline the factors that promote and hinder exclusive breastfeeding in developing country. Methodology: Methodology used is literature review. To find studies from January 2012 to December 2022, searches were done in Science Direct, Proquest, Google Scholar, and PubMed. Both qualitative and quantitative research was taken into account, and analyzed using NVivo. Results: Factors driving the success of exclusive breastfeeding are rooming-in, antenatal attendance, husband or family support, peer support, timely breastfeeding initiation. Meanwhile, the inhibiting factors for exclusive breastfeeding in developing countries are introducing food too early, maternal physical condition, working mothers, influence of grandmother, assumed insufficient breastmilk, cultural beliefs and practices, earlier bottle usage, inadequate infant weight gain, joint family, lack of family support, lack of workplace support, mode of delivery, and mother's psychological factors. Limitations: Researchers were unable to determine if the reference used as the source was biased. Contribution: According to this study, there are still a number of barriers that women must overcome in order to breastfeed their babies exclusively for up to six months, and there are motivating aspects that must be enhanced to promote the success of exclusive breastfeeding. The findings of this study can be applied to the creation of strategies and treatments for dealing with challenges in exclusive breastfeeding.